Changes in non-opioid substitution treatment episodes for pharmaceutical opioids and heroin from 2002 to 2011. (1st April 2015) - Nielsen, S.; Roxburgh, A.; Bruno, R.; Lintzeris, N.; Jefferson, A.; Degenhardt, L.
Highlights: There were important differences between heroin and pharmaceutical opioid (PO)s. Those using codeine differed substantially from those using stronger opioids, such as oxycodone. Notable changes over time were observed with demographic characteristics for episodes. PO episodes were more likely to be short-term (e.g. detoxification, assessment). Dynamic changes over time highlight the importance of ongoing monitoring. Abstract: Background: There has been a well-documented increase in the non-medical use of pharmaceutical opioids (PO) worldwide. However, there has been little detailed examination of treatment demand, or the characteristics of those presenting for treatment, particularly for treatments other than opioid substitution. Methods: Data from closed drug and alcohol treatment episodes from the Alcohol and Other Drug Treatment Services National Minimum Data Set (AODTS-NMDS, representing non-opioid substitution treatment) in Australia for 2002–2003 to 2010–2011 were examined. In the four jurisdictions where detailed data were available, episodes where heroin was the principal drug of concern were compared to episodes for the four most frequently reported pharmaceutical opioids (morphine, codeine, fentanyl and oxycodone). Results: In 2002–2003, most (93%) opioid treatment was related to heroin with seven percent of all opioid treatment episodes reporting a PO as the principal drug of concern. In 2010–2011, 20% of all opioid treatment episodes were attributed to POs. Distinct changes over time were observed for different opioids. There was an increase in the average age at the start of treatment for heroin and oxycodone episodes, and a reduction in the proportion of females for codeine episodes, with 67% in 2002–2003 compared with 44% in 2010–2011. Codeine and oxycodone episodes had the lowest current or past injection rates. Conclusions: Clear differences were observed over time and between different opioids. Monitoring these emerging patterns will be important to inform treatment needs, particularly in light of different patterns of poly drug use, different routes of administration and changing demographic characteristics.